2004
DOI: 10.1111/j.1365-2729.2004.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intrinsic motivation on e‐learning in authentic computer tasks

Abstract: Students with high intrinsic motivation often outperform students with low intrinsic motivation. However, little is known about the processes that lead to these differences. In education based on simulations or authentic electronic learning environments, this lack of insight is even more clear. The present study investigated what students actually did in an electronic learning environment that was designed as a game-like realistic simulation in which students had to play the role of a junior consultant. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
142
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(175 citation statements)
references
References 48 publications
8
142
0
4
Order By: Relevance
“…the perceived experience that a learner's behaviour is self-determined, autonomous, or intrinsically motivated) has a strong impact on learning outcomes Liu, Horton, Olmanson, & Toprac, 2011;Martens, Gulikers, & Bastiaens, 2004;Rienties, Tempelaar, Van den Bossche, Gijselaers, motivation, that is a drive to learn based on the satisfaction and pleasure of the activity of learning itself rather than external rewards, significantly predicted science knowledge post-test scores in a blended science game. found that perceived autonomy of 262 learners was the most significant factor predicting learning outcomes in two distance education programmes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…the perceived experience that a learner's behaviour is self-determined, autonomous, or intrinsically motivated) has a strong impact on learning outcomes Liu, Horton, Olmanson, & Toprac, 2011;Martens, Gulikers, & Bastiaens, 2004;Rienties, Tempelaar, Van den Bossche, Gijselaers, motivation, that is a drive to learn based on the satisfaction and pleasure of the activity of learning itself rather than external rewards, significantly predicted science knowledge post-test scores in a blended science game. found that perceived autonomy of 262 learners was the most significant factor predicting learning outcomes in two distance education programmes.…”
mentioning
confidence: 99%
“…While an increasing number of studies have indicated that self-determination of learners influences learning outcomes, only a limited number of studies have focussed on the role of self-determination in actual social interaction processes and behaviour of learners in CMC (Järvelä et al, 2011;Martens et al, 2004;Renninger, Cai, Lewis, Adams, & Ernst, 2011;Rienties, 2010). In order to better understand why drop-out rates in CMC are substantial (Nagel, Blignaut, & Cronjé, 2009;Rovai, 2003), and how teachers can design learning environments that continuously motivate learners to actively engage with the task (Järvelä & Häkkinen, 2002;Kirschner, Strijbos, Kreijns, & Beers, 2004;Liu et al, 2011;Nagel et al, 2009), we argue that it is important to understand the complex learning dynamics that occur in CMC and how the degree of self-determination influences behaviour of learners and teams in online settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the many existing contents delivery ways such as internet-based, multimedia, social media, and virtual/augmented reality (Bermejo, 2005;Blank, et al, 2003;Bressler and Bodzin, 2013;Caeiro-Rodríguez, et al, 2013;Chen, et al, 2017;Chen, et al, 2015;Clark and Mayer, 2011;Denner, et al, 2012;Gao and Liu, 2010;Lee, et al, 2016;Mao, et al, 2017;Martens, et al, 2004;Romero-Hall, et al, 2016;Stash, et al, 2004), the standardized ePUB3 format (ePUB3 Overview, 2011) is a newly introduced specification as a distribution and interchange format standard for digital publications and documents. It defines a means of representing, packaging, and encoding structured and semantically enhanced Web contents -including HTML5, CSS, SVG, images, and other resources -for distributions in a single-file format.…”
Section: Epub3 Ebookmentioning
confidence: 99%
“…In this sense video games can be a very helpful learning tool, as long as motivation is a key aspect of effective learning (Cordova and Lepper 1996;Martens, Gulikers et al 2004). It is commonly agreed that an intrinsic advantage of game based learning over more traditional approaches to learning is that games are motivating (Malone 1982;Malone and Lepper 1987;Garris, Ahlers et al 2002).…”
Section: Game-based Learningmentioning
confidence: 99%